(untitled) (Innovation & Development in Engineering and Applied Science, 2024)
In this work, augmented reality is applied to offer enveloping and participatory learning experiences through virtual environments or elements that complement the real world with digital content. It has been a documentary, exploratory, descriptive, and, in the pilot stage, with a qualitative approach. Technical information was collected on the various digitized and accessible topics through the ITCA Academy application, where the user receives the default information through electronic devices. The participants were satisfied with what was observed and said they processed the information received through immersive education. The understanding of the participants was superior compared to traditional teaching, minimizing the inconveniences of the teaching-learning process through the use of the application. The practical implementation of immersive education, with its interactive resources, covered the failures of traditional education, causing novel results in the teaching-learning process.